Intelligent parcel dropbox / Mohamad Ridzuan Rashid … [et al.] - Rashid, Mohamad Ridzuan; Rosly, Muhammad Aliff; Abdullah, Shukriah; Ariffin, Mohd Arzaimiruddin; Mohammed Redza, Mohd Ridhwan (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
In response to the COVID-19 pandemic, several restrictions and standard operating procedures (SOPs) have been enforced during the MCO, such as the economic and social activities restriction, compulsory mask-wearing, and social distancing. These restrictions and SOPs has pushed many activities previously undertaken offline to the online realm. This includes shifting from in-person shopping to ordering goods and services online, leading to a remarkable increase in e-commerce orders for this year. Therefore, the Intelligent Parcel Drop Box is developed to allow better MCO SOPs compliance and reduce the probability of virus transmission during the delivery process as well as to increase the efficiency of delivery process among courier staff. This Drop Box is designed using CAD Modelling software, and the functionality of the control system is demonstrated using Proteus Design Suite software. It features a motor-controlled roller shutter door to maximize space usage and a pump-controlled disinfection antiseptic spray to sanitize the received goods. The user interface control system is manifested in two ways; a user-friendly physical interface (at the Drop Box) and an Internet of Things (IoT) based virtual interface (at the mobile phone). The physical interface allows a delivery person to interact with Drop Box during the delivery process physically. While the latest cutting-edge IoT technology enables remote control using a virtual interface, even the user is far away. The findings of this study will be marked as a significance endeavor for the advancement of how technology is changing the delivery industry and along with, it will largely contribute to the continuous improvement in parcel delivery method. Delivery flexibility with automated service-one that takes a package right to a customer’s front door in a way that’s entirely safe from infections, accurate tracking and economical.